Penerapan Hukum Positif Indonesia Terhadap Kasus Kejahatan Dunia Maya Deepfake - Shannon Gandrova; Ricky Banke (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The development of yechnology science is unable to be separated from modern human life in this 21st century. Nearly every aspect of human daily life is the product of technology science. Technology was first presented and created with the purpose of making human life easier. It is both beneficial and detrimental at the same time because the limitlessness of the internet is prone to be misused. For instance, deepfake technology is used to commit fraud. Deepfake is a sophisticated technology that has the ability to manipulate a person’s photos, videos, and voice. University College London (UCL) ranks the threat of deepfakes as one of the biggest threats facing society today. With the ability to immitate voices and change digital content, deepfake is used to spread pornographic content, extort money, or spread misinformation to the public. Many individuals abuse this technology to take other people’s data non-consensually and use it secretly to carry out criminal acts. The intelligance of criminals gives birth to new types of crimes that are fraudulent and are able to manipulate the evidence used in trials. Coupled with the anonymous feature on the internet, crimes can be committed more easily and complicate the investigation process to apprehend the perpetrator. To stop the spread of misinformation from processed deepfakes, a responsive role is required from police and government officials. Therefore, advances of the internet need to be accompanied by cyber protection and stricter legal regulation. The relentless progress of internet technology has given rise to new types of crimes that need relevant legal updates.